Partnership in public sector agricultural R&D: evidence from India - Janaiah, Aldas; Hossain, Mahabub (2004)
This paper broadly explores the hypothesis that scientists working together for a common cause can do wonders in a group, if the system is fairly transparent and institutionalised. As a case study, it assesses the synergetic effects of partnership research in public sector R&D in India, with the all-India coordinated rice improvement programme as an example. The study finds that the partnership mechanism of AICRIP has played an important role through free interstate and inter-institutional movement of improved germplasm, which has accelerated the adoption of modern varities of rice for cultivation in many parts of India. - Reproduced.
Keywords: Research centres; Scientific cooperation; Research and development; Public private partnership; Public enterprises; Agricultural research